2022
DOI: 10.1177/09697330211035489
|View full text |Cite
|
Sign up to set email alerts
|

Moral distress interventions: An integrative literature review

Abstract: Moral distress has been well reviewed in the literature with established deleterious side effects for all healthcare professionals, including nurses, physicians, and others. Yet, little is known about the quality and effectiveness of interventions directed to address moral distress. The aim of this integrative review is to analyze published intervention studies to determine their efficacy and applicability across hospital settings. Of the initial 1373 articles discovered in October 2020, 18 were appraised as r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 106 publications
0
12
0
Order By: Relevance
“…Health leaders must acknowledge the moral dimensions of clinicians’ experiences during the pandemic and provide workplace support to counter reactive behaviours such as self-preservation responses, shutting down, disengaging, and avoiding patients 9. In healthcare, interventions that have been reported as mitigating moral distress include educational interventions, facilitated discussions of 30-60 minutes, specialist consultation services, multidisciplinary rounds, self-reflection, and narrative writing 21222324…”
Section: Strategies To Repair Moral Lossmentioning
confidence: 99%
“…Health leaders must acknowledge the moral dimensions of clinicians’ experiences during the pandemic and provide workplace support to counter reactive behaviours such as self-preservation responses, shutting down, disengaging, and avoiding patients 9. In healthcare, interventions that have been reported as mitigating moral distress include educational interventions, facilitated discussions of 30-60 minutes, specialist consultation services, multidisciplinary rounds, self-reflection, and narrative writing 21222324…”
Section: Strategies To Repair Moral Lossmentioning
confidence: 99%
“…14,15 The positive impact of cognitive coping strategies which involve reflection on and meaning making of moral distress has been described as well. 13,14,16,17 The most recent focus of interest has been the cultivation of moral resilience to sustain and restore moral integrity. 16,18 Moral resilience refers to “the capacity of an individual to sustain or restore their integrity in response to moral confusion, complexity, distress or setbacks.” (p. 581) 19 Going beyond an individualistic conception of moral resilience, Sala Defilippis et al have proposed that moral resilience is a virtuous character trait, which allows nurses to “remain open for compromises with themselves and with the given situation without compromising their own moral integrity.” (p.8) 20 This broadened perspective acknowledges moral uncertainty and ambiguity.…”
Section: Introductionmentioning
confidence: 99%
“…10,12,13 Today, a few articles have discussed and evaluated interventions aimed at minimizing moral distress at both individual and institutional levels. 14,15 The positive impact of cognitive coping strategies which involve reflection on and meaning making of moral distress has been described as well. 13,14,16,17 The most recent focus of interest has been the cultivation of moral resilience to sustain and restore moral integrity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 The existence of nurses’ moral distress is critically important to pay attention to because it can influence clinical decisions, increase the possibility of medical errors, and ultimately increase the risk of fatigue experienced by nurses. 13 , 14 Moral distress has been widely reviewed across many care contexts, but no study was found on the issues of moral distress among nurses in a pandemic situation like a COVID-19 pandemic .…”
Section: Introductionmentioning
confidence: 99%